Murder, Extermination, And Torture As The Underlying Offenses Of Crimes Against Humanity: A Practical Reflection On The International Crimes Tribunal Bangladesh (Journal of Namibian Studies : History Politics Culture, 2023)
The current government of Bangladesh introduced a criminal tribunal, the International Crimes Tribunal Bangladesh (ICTB), in 2010, aiming to try and penalize the offenders of crimes against humanity committed in the Liberation War of Bangladesh in 1971. Generally, crimes against humanity are perpetrated by a natural person, not by an intangible entity. Establishing each element of a specific criminal act is essential to prove such crimes’ guilt and punish the criminal. Hence, this study analyzes the elements of murder, extermination, and torture as the underlying offenses of crimes against humanity according to international customary law and the ICTB Statute. By applying a qualitative approach through scrutinizing leading cases from international criminal tribunals and ICTB, this study first scrutinizes the latest international customary law development outlined by international criminal tribunals on these offenses. Secondly, this study examines whether the ICTB is applying specific requirements of such underlying offenses of crimes against humanity with the latest development enshrined by international criminal law and tribunals. Thirdly, this study examines any legal failure ascertained by the ICTB to apply elements of specific offenses of crimes against humanity that are internationally known as the established norm before proving crimes against humanity as major international crimes. Then, this study finally recommends some ways forward; otherwise, the ICTB would be considered the victor's justice type of initiative to suppress the alleged perpetrators, mainly from the opposition political party of Bangladesh.